Online Monitoring on a PV-based Smart Grid System - Hadi Pramono, Sholeh; Maulana, Eka; Dwi Nusantoro, Goegoes; Nainy Sari, Sapriesty (International Journal of Engineering and Technology, 2018)
Optimizing the use of energy in a PV-based smart grid system using an online monitoring is described in this paper. This technique is based on the power monitoring using the client server experimental verification. Sensors are used to monitor the load voltage and current giving the power value. This kind of monitoring system can be done via online system based on web server and ubiquitous access. In this research, the mechanism of monitoring has been carried out through the wireless communication system. An internet Wi-Fi module has been made accessible through website to effectuate this kind of monitoring mechanism. Such monitoring system is prospective to be used in Internet of Things (IoT)-based smart grid networks in the future. The proposed system in this study results in a current reading range up to 30A, and voltage Â up to 30V. The read data have been stored in a memory card of microcontroller system, producing a data logging system and supporting the data sending through the web service for real-time monitoring system wirelessly.Â Â Â